Docetaxel and Cisplatin in First Line Treatment of Patients with Unknown Primary Cancer: A Multicenter Study of the Anatolian Society of Medical Oncology - (:unkn) unknown (ASIAN PACIFIC ORGANIZATION CANCER PREVENTION, 2014)
Background: The overall prognosis for cancers of unknown primary (CUP) is poor, median overall survival (OS) being 6-12 months. We evaluated our multicentric retrospective experience for CUP administered docetaxel and cisplatin combination therapy. Materials and Methods: A total of 29 patients that were pathologically confirmed subtypes of CUP were included in the study. The combination of docetaxel (75 mg/m(2), day 1) and cisplatin (75 mg/m(2), day 1) was performed as a first line regimen every 21 days. Results: The median age was 51 (range: 27-68). Some 17 patients had multimetastatic disease on the inital diagnosis. Histopathological diagnoses were well-moderate differentiated adenocarcinoma (51.7%), undifferentiated carcinoma (27.6%), squamous cell cancer (13.8%), mucoepidermoid carcinoma (3.4%) and neuroendocrine differentiated carcinoma (3.4%). Median number of cycles was 3 (range: 1-6). Objective response rate was 37.9% and clinical benefit was 58.6%. Median progression free survival (PFS) and overall survival (OS) were 6 months (range: 4.3-7.7 months) and 16 months (range: 8.1-30.9 months), respectively. Fourteen patients (60.8%) were treated in a second line setting. There was no treatment related death. Most common toxicities were nausia-vomiting (44.6%) and fatigue (34.7%), serious cases (grade 3/4) suffering nausia-vomiting (10.3%), neutropenia (13.8%) and febrile neutropenia (n=1). Conclusion: The combination of cisplatin and docetaxel is an effective regimen for selected patients with CUP.
Keywords: Cancer of unknown primary; docetaxel; cisplatin; combination; clinical benefit; PHASE-II TRIALS; PRIMARY SITE; CARCINOMA; SURVIVAL; CHEMOTHERAPY; CARBOPLATIN; PACLITAXEL; EFFICACY